A Newly Identified MicroRNA, mmu-miR-7578, Functions as a Negative Regulator on Inflammatory Cytokines Tumor Necrosis Factor-α and Interleukin-6 via Targeting Egr1 in Vivo - Zhang, Jinsong (American Society for Biochemistry and Molecular Biology, 2013)
Appropriate innate immune responses are required to protect an organism against foreign pathogens, and the immune response must be tightly controlled. Here, we report a new microRNA (miRNA) identified from a small RNA library from the epididymis, termed miR-7578, that acts as a negative regulator of inflammatory responses. It was abundantly expressed in immune-related organs and induced by lipopolysaccharide in the lung and epididymis, as well as macrophages stimulated with diverse Toll-like receptor ligands, in an NF-κB-dependent manner. mmu-miR-7578 inhibited the release of pro-inflammatory cytokines, including TNFα and IL6, by regulating its target gene Egr1, which encodes a transcription factor that activates TNFα and NF-κB expression. Transgenic mice overexpressing mmu-miR-7578 displayed higher resistance to endotoxin shock and lower plasma levels of TNFα and IL6, indicating that this miRNA acted as a negative molecule of immune response. In sum, we report a previously uncharacterized LPS-responsive miRNA that controls inflammatory response in a feedback loop by fine-tuning a key transcription factor in vivo.